Identification of the LOX Gene Family in Peanut and Functional Characterization of AhLOX29 in Drought Tolerance - Yifei Mou; Quanxi Sun; Cuiling Yuan; Xiaobo Zhao; Juan Wang; Caixia Yan; Chunjuan Li; Shihua Shan (Frontiers in Plant Science, 2022)
Lipoxygenases (LOXs) are a gene family of nonheme iron-containing dioxygenases that play important roles in plant development and defense responses. To date, a comprehensive analysis of LOX genes and their biological functions in response to abiotic stresses in peanut has not been performed. In this study, a total of 72 putative LOX genes were identified in cultivated (Arachis hypogaea) and wild-type peanut (Arachis duranensis and Arachis ipaensis) and classified into three subfamilies: 9-LOX, type I 13-LOX and type II 13-LOX. The gene structures and protein motifs of these peanut LOX genes were highly conserved among most LOXs. We found that the chromosomal distribution of peanut LOXs was not random and that gene duplication played a crucial role in the expansion of the LOX gene family. Cis-acting elements related to development, hormones, and biotic and abiotic stresses were identified in the promoters of peanut LOX genes. The expression patterns of peanut LOX genes were tissue-specific and stress-inducible. Quantitative real-time PCR results further confirmed that peanut LOX gene expression could be induced by drought, salt, methyl jasmonate and abscisic acid treatments, and these genes exhibited diverse expression patterns. Furthermore, overexpression of AhLOX29 in Arabidopsis enhanced the resistance to drought stress. Compared with wide-type, AhLOX29-overexpressing plants showed significantly decreased malondialdehyde contents, as well as increased chlorophyll degradation, proline accumulation and superoxide dismutase activity, suggesting that the transgenic plants exhibit strengthened capacity to scavenge reactive oxygen species and prevent membrane damage. This systematic study provides valuable information about the functional characteristics of AhLOXs in the regulation of abiotic stress responses of peanut.